Profitability, Leverage, and Firm Value: the Mediating Role of Dividend Policy : A Case Study of the Energy Sector Listed on the Indonesia Stock Exchange for the Period 2021–2024 - Berardy Rheandri Laiman; I Made Surya Negara Sudirman (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze the effect of profitability, leverage, and dividend policy on firm value in the energy sector listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The energy sector was selected due to its strategic role in the national economy and its contribution to the Composite Stock Price Index (IHSG). Out of 81 energy sector firms, 22 firms were obtained as samples using a purposive sampling method. Data analysis was conducted using the path analysis technique. The results show that profitability has a significant effect on firm value, while leverage has no effect. Dividend policy also has no effect on firm value, whereas profitability has no effect on dividend policy, and leverage has a significant negative effect on dividend policy. Furthermore, dividend policy is unable to mediate the relationship between profitability and leverage with firm value. These findings imply that firm value is more influenced by profitability factors than by leverage or dividend policy. The results of this study are expected to serve as a reference for firm management, investors, and policymakers in making future financial decisions.